STRESS-STAIN STATE MONITORING SYSTEM OF COMPOSITE STRUCTURES WITH THE MECHANOLUMINESCENT SENSORS - N. Yu. Makarova; B. I. Shakhtarin (Научный вестник МГТУ ГА)
At present, the intensive use of composite materials for the creation of various parts of aviation equipment is noted. The irreplaceability of composites is provided by a combination of such important characteristics as high mechanical strength, heat resistance, corrosion resistance, low density. Due to its complex structure, composite panels can have the intellectual property of self-diagnostics of their condition. Structurally, the composite panel is a matrix reinforced with fibers. Optical sensors embedded into composite matrix transmit radiation trough the reinforcing glass fiber. So, an autonomous information-measuring system can be created. To control the stress-strain state of composite structures, it is proposed to incorporate mechanoluminescent sensors into the structure of composites. The phosphors of the AIIBVI group possess the ability to generate radiation under mechanical loading (mechanoluminescence). Such sensors are light-generating, non-volatile, solid-state, miniaturized. When the composite structure is deformed, the sensors generate mechanoluminescent radiation transmitted along the reinforcing fibers to the photodetector device and to the signal processing unit, in which the localization and magnitude of the mechanical action on the composite panel are analyzed. The physical principles of mechanoluminescent sensor elements are described in the article, a mathematical model of transformation is presented, which allows calculating the output light flux of the sensor under mechanical actions of different duration and magnitude. On the basis of the mathematical model, an application is realized in the MATLAB for modeling the optical signal of sensors with different parameters when the amplitude-time parameters of the input effect change. According to the mathematical model, an algorithm for processing the signal of a mechanoluminescent sensor has been developed, which makes it possible to perform an inverse transformation – to restore the parameters of the input mechanical action by the light flux.